Looking at Spain - Powell, Jillian (Milwaukee, WI Gareth Stevens Publishing, 2007)
Spain has more than ten thousand castles. Readers will see the snowy Sierra Nevada, the sunny Costa del Sol, the vast Meseta, and the historic cities of Madrid, Barcelona, and Seville. Learn about life in Spain, from the Bay of Biscay to the Balearic Islands and from plazas to paella.
Elementary
Keywords: Spain; Spain - Social life and customs